Press Freedom and Journalist Independence in Medan, Indonesia - Sikumbang, Ahmad Tamrin; Wal Hidayat, Taufik; Kholil, Syukur; Samosir, Hasrat Efendi (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This study aims to analyze the application of journalists in carrying out journalistic duties in Medan City. The research method used is descriptive with a qualitative approach. The research informants were ten people who were determined purposively. Observation, interviews, and documentation are data collection. Data analysis refers to the Milles-Hubberman model: data reduction, data presentation, drawing, and testing conclusions. The results of research on the application of journalists in carrying out journalistic duties in Medan City cannot be realized in totality because there are conflicts of interest, such as the interests of media authorities, advertisers, and the government who drive the news and the personal interests of journalists. It is possible to implement the independence of journalists with the style of writing Feature news (typical essays).